Light‐Induced Degradation of Polymer:Fullerene Photovoltaic Devices: An Intrinsic or Material‐Dependent Failure Mechanism?. Issue 18 (14th August 2014) - Voroshazi, Eszter; Cardinaletti, Ilaria; Conard, Thierry; Rand, Barry P.
<x xml:space="preserve">Abstract</x> Although degradation mechanisms in organic photovoltaic devices continue to receive increased attention, it is only recently that the initial light‐induced failure, or so‐called burn‐in effect, has been considered. Both prototypical polythiophene:fullerene and polycarbazole:fullerene systems exhibit an exponential performance loss of ≈40% upon 150 h of continuous solar illumination. While the decrease in both the short‐circuit current (JSC) and open‐circuit voltage (VOC) is the origin of performance loss in poly(3‐hexylthiophene):[6, 6]‐phenyl‐C61‐butyric acid methyl ester (P3HT:PC60BM), in poly(N‐9′‐hepta‐decanyl‐2, 7‐carbazole‐alt‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)):[6, 6]‐phenyl‐C71‐butyric acid methyl ester (PCDTBT:PC70BM) the decline of the fill factor dominates. By systematic variation of the interface layers, active layer thickness, and acceptor in polythiophene:fullerene cells, the loss in JSC is ascribed to a degradation in the bulk of the P3HT:PC60BM, while the drop in VOC is reversible and arises from charge trapping at the contact interfaces. By replacing the C60 fullerene derivative with a C70 derivative, or by modifying the electron transport layer, the JSC or VOC, respectively, are stabilized. These insights prove that the burn‐in process stems from multiple concurrent failure mechanisms. Comparing the ageing and recovery processes in P3HT and PCDTBT blends results in the conclusion that their interface failures differ in nature and that burn‐in is a material dependent, rather than an intrinsic, failure mechanism.